Photon 2001 : Proceedings of the International Conference on the Structure and Interactions of the Photon, Including the 14th International Workshop on Photon-photon Collisions Ascona, Switzerland 2-7 September 2001. - Kienzle-Focacci, Maria-Novella (World Scientific Publishing Company, 2002)
This volume reports on all aspects of high energy photon interactions using both photon and proton targets. Significant new results from the LEP and HERA experiments as well as from CLEO II and BELLE are presented. These data are confronted with diverse theoretical models. In particular, predictions of QCD in both the perturbative and the non-perturbative sector are extensively discussed. The prospects for gamma-gamma physics at future high energy colliders are also reviewed. In total 72 papers are collected. The proceedings have been selected for coverage in:. Index to Scientific & Technical.